Creative advertising visualization as a medium to promote innovation & creativity gallery at UiTM Shah Alam, Selangor / Muhammad Shaiful Nizam Azaddin - Azaddin, Muhammad Shaiful Nizam (2013)
Gallery is the latest information on the result of innovation or new products to be highlighted and commercialized to the local community and outside. Disagree on the situation in the museum as the place to take care of monuments or artefacts' result of historical relics. In this regard, the researcher would like to make an assessment of the situation, interaction and expression the visitors to the gallery to see and find out the latest information on the revenue product innovation researchers an exhibitor at the galleries Universiti Teknologi MARA, Shah Alam, Selangor. The aims on this research is the advertising context, globalization has influenced the cultural identity of a country through the use of a global brand. Differences between countries and cultures have been set aside by reason of consumers around the world are motivated by the same desires and needs. This view has mobilized a great interdisciplinary debate among advocator, academics, and even advertisers and advertising practitioners. This research study has use the qualitative and quantitative in experimental base on promotion advertising focus on and promote others education place such as Gallery of Innovation and Creativity, UiTM Shah Alam. Findings indicate identity in the implementation of their advertising creative, creative approach to foreign. In addition, there are also elements of Asian standardization found in this study. Positive goal to find out the view from all angles and the numbers of visitors in the gallery in order to repair and improve the quality of services to the public gallery, both inside and outside the country in order to image galleries UiTM to the international level commercialization. The conclusion, assessments, observations, and insights from the study as well as visitors expression in value from time to time to improve the structuring and management by the gallery at UiTM, in line with the goal of making the University Technology University towards a world-class entrepreneurship with high education levels.